Kekerasan Berbasis Gender terhadap Anak dan Perempuan: Antara Stigma Sosial dan Ketimpangan Perlindungan Hukum - Arman Hanapi; Roy Marthen Moonti; Ibrahim Ahmad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Gender-based violence against women and children is a serious problem in Indonesia that reflects the inequality of social structures and the weakness of legal implementation. This study aims to examine the extent to which the Indonesian legal system is able to provide fair, equal, and gender-responsive protection to victims of violence, as well as assess the challenges in its application. The type of research used is a normative-critical study with a Feminist Legal Theory approach. The results of the analysis show that although there are regulatory advances such as the TPKS Law and the Presidential Instruction on Gender Mainstreaming, their application is still biased, not victim-friendly, and lacks a gender perspective. In conclusion, the law in Indonesia has not fully guaranteed substantive justice for victims. Therefore, it is recommended that legal reforms based on victims' experiences, increasing the capacity of law enforcement officials, and strengthening victim service institutions to encourage inclusive and transformative justice.